Geotechnical engineering : principles and practices - Coduto, Donald P.; Yeung, Man-Chung, 1965-; Kitch, William A. (Upper Sadddle River : Pearson, 2011)
This introductory geotechnical engineering textbook explores both the principles of soil mechanics and their application to engineering practice. It offers a rigorous, yet accessible and easy-to-read approach, as well as technical depth and an emphasis on understanding the physical basis for soil behavior.
Chapter 1 Introduction to Geotechnical Engineering -- Chapter 2 Engineering Geology -- Chapter 3 Site Exploration and Characterization -- Chapter 4 Soil Composition -- Chapter 5 Soil Classification -- Chapter 6 Excavation, Grading, and Compacted Fill -- Chapter 7 Groundwater-Fundamentals and One-Dimensional Flow -- Chapter 8 Groundwater-Multidimensional Flow and Applications -- Chapter 9 Stress -- Chapter 10 Compressibility and Settlement -- Chapter 11 Rate of Consolidation -- Chapter 12 Soil Strength -- Chapter 13 Stability of Earth Slopes -- Chapter 14 Foundations -- Chapter 15 Spread Footing Design -- Chapter 16 Earth Retaining Structures -- Chapter 17 Lateral Earth Pressures.
Includes bibliographical references (p. 765-778) and index.
1
Keywords: Engineering geology